Reliability of phenotypic early‐onset ataxia assessment: a pilot study. (21st May 2015) - Lawerman, Tjitske F; Brandsma, Rick; van Geffen, Joke T; Lunsing, Roelineke J; Burger, Huibert; Tijssen, Marina A J; de Vries, Jeroen J; de Koning, Tom J; Sival, Deborah A
Abstract : Aim: To investigate the interobserver agreement on phenotypic early‐onset ataxia (EOA) assessment and to explore whether the Scale for Assessment and Rating of Ataxia (SARA) could provide a supportive marker. Method: Seven movement disorder specialists provided independent phenotypic assessments of potentially ataxic motor behaviour in 40 patients (mean age 15y [range 5–34]; data derived from University Medical Center Groningen medical records 1998–2012). We determined interobserver agreement by Fleiss' kappa. Furthermore, we compared percentage SARA subscores ([subscore/total score]×100%) between 'indisputable' (primary ataxia recognition by at least six observers) and 'mixed' (ataxia recognition, unfulfilling 'indisputable' criteria) EOA phenotypes. Results: Agreement on phenotypic EOA assessment was statistically significant ( p <0.001), but of moderate strength (Fleiss' kappa=0.45; 95% CI 0.38–0.51). During mild disease progression, percentage SARA gait subscores discriminated between 'indisputable' and 'mixed' EOA phenotypes. In patients with percentage SARA gait subscores >30%, primary ataxia was more frequently present than in those with subscores <30% ( p =0.001). Interpretation: Among movement‐disorder professionals from different disciplines, interobserver agreement on phenotypic EOA recognition is of limited strength. SARA gait subscores can provide a supportive discriminative marker between EOA phenotypes. Hopefully, future phenotypic insight will contribute to the inclusion of uniform, high‐quality data in international EOA databases. What this paper adds: Interobserver agreement on phenotypic early‐onset ataxia (EOA) assessment is statistically significant. The strength of EOA interobserver agreement is interpreted as limited. Gait subscores on the Scale for Assessment and Rating of Ataxia can support phenotypic EOA assessment. This article is commented on by Musselman on pages11–12 of this issue.